Insincere commitments : human rights treaties, abusive states, and citizen activism - Smith-Cannoy, Heather M. (Georgetown University Press, 2012)
Paradoxically, many governments that persistently violate human rights have also ratified international human rights treaties that empower their citizens to file grievances against them at the United Nations. Therefore, citizens in rights-repressing regimes find themselves with the potentially invaluable opportunity to challenge their government's abuses. Why would rights-violating governments ratify these treaties and thus afford their citizens this right? Can the mechanisms provided in these treaties actually help promote positive changes in human rights?Insincere Commitments uses both quant.